123 No hit zones: an innovative approach to violence prevention. (5th May 2020) - Fleckman, Julia; Ruiz, Rachael; Leblanc, Stacie; Gilbert, Hannah; Taylor, Catherine
Abstract : Statement of Purpose: No Hit Zones (NHZs) are an emergent and highly promising public health strategy designed to change community-level social norms regarding the acceptability of physical punishment of children, an important approach for child physical abuse (CPA) prevention. NHZs are a multi-tiered strategic approach designed to: (1) promote an environment of safety such that no one will be hit, or witness hitting, within an organizational or community setting, and (2) reduce acceptance and use of PP within that setting, thereby ultimately reducing the incidence of CPA. This presentation will discuss the benefits and challenges of NHZ implementation, training resources available to implement an NHZ, and preliminary results from a NHZ evaluation at Children's Hospital of New Orleans. Methods/Approach: Training resources developed and results from a short-term evaluation of the NHZ intervention will be presented. Pre- and post-assessments were administered to all medical center staff invited to participate in the study (n=507) before and after a mandatory NHZ training. Measures were included to assess staff attitudes toward physical punishment, attitudes toward medical staff intervention when parents hit children, medical center policy and access to information on discipline, frequency of witnessing a parent hitting a child on the medical center property and whether or not they had intervened. Results: A pre-post analysis was completed via paired t-test, with significant results (p<0.001) for a reduction in positive attitudes toward physical punishment, an increase in positive attitudes toward medical staff intervention when parents hit children, and willingness to intervene. Conclusions: The current results demonstrate promise for NHZs in reducing community-level risk for CPA. Significance and Contributions to Violence and Injury Prevention Science: NHZs are an innovative approach to family violence prevention at the community level. This presentation will discuss development of and preliminary results from the intervention evaluation.